Question Number 80543 by Power last updated on 04/Feb/20 | ||
Commented by mr W last updated on 04/Feb/20 | ||
$$\mathrm{1010} \\ $$ | ||
Commented by Power last updated on 04/Feb/20 | ||
$$\mathrm{solution}\:\mathrm{sir} \\ $$ | ||
Commented by jagoll last updated on 04/Feb/20 | ||
$${let}\:\sqrt{{x}^{\mathrm{2}} −{x}}\:={t} \\ $$$$\left({t}−\mathrm{2}\right)\left({t}−\mathrm{4}\right)\left({t}−\mathrm{6}\right)...\left({t}−\mathrm{2020}\right)=\mathrm{1} \\ $$ | ||
Commented by jagoll last updated on 04/Feb/20 | ||
$$ \\ $$$$\underset{{t}=\mathrm{1}} {\overset{\mathrm{1010}} {\sum}}{t}_{{i}} \:=\:\mathrm{2}+\mathrm{4}+\mathrm{6}+...+\mathrm{2020} \\ $$ | ||
Commented by mr W last updated on 04/Feb/20 | ||
$${correct}\:{is}: \\ $$$$\underset{{t}=\mathrm{1}} {\overset{\mathrm{1010}} {\sum}}{t}_{{i}} \:=−\left(\mathrm{2}+\mathrm{4}+\mathrm{6}+...+\mathrm{2020}\right) \\ $$ | ||
Commented by jagoll last updated on 04/Feb/20 | ||
$${oo}\:{yes}\:{sir}.\:{thank}\:{you} \\ $$ | ||
Answered by mr W last updated on 04/Feb/20 | ||
$${let}\:\sqrt{{x}^{\mathrm{2}} −{x}}=\mathrm{2}{z} \\ $$$$\left(\mathrm{2}{z}−\mathrm{2}\right)\left(\mathrm{2}{z}−\mathrm{4}\right)...\left(\mathrm{2}{z}−\mathrm{2020}\right)=\mathrm{1} \\ $$$$\mathrm{2}^{\mathrm{1010}} \left({z}−\mathrm{1}\right)\left({z}−\mathrm{2}\right)...\left({z}−\mathrm{1010}\right)=\mathrm{1} \\ $$$$\left({z}−\mathrm{1}\right)\left({z}−\mathrm{2}\right)...\left({z}−\mathrm{1010}\right)−\frac{\mathrm{1}}{\mathrm{2}^{\mathrm{1010}} }=\mathrm{0} \\ $$$${this}\:{eqn}.\:{has}\:\mathrm{1010}\:{roots}\:{for}\:{z},\:{say} \\ $$$${z}_{\mathrm{1}} ,{z}_{\mathrm{2}} ,...,{z}_{\mathrm{1010}} \\ $$$$\underset{{i}=\mathrm{1}} {\overset{\mathrm{1010}} {\sum}}{z}_{{i}} =−\left(\mathrm{1}+\mathrm{2}+...+\mathrm{1010}\right)=−\mathrm{510555} \\ $$$$\underset{{i}=\mathrm{1}} {\overset{\mathrm{1010}} {\prod}}{z}_{{i}} =\mathrm{1}×\mathrm{2}×...×\mathrm{1010}−\frac{\mathrm{1}}{\mathrm{2}^{\mathrm{1010}} }=\mathrm{1010}!−\frac{\mathrm{1}}{\mathrm{2}^{\mathrm{1010}} } \\ $$$$ \\ $$$$\sqrt{{x}^{\mathrm{2}} −{x}}=\mathrm{2}{z}_{{i}} \:\:\left({i}=\mathrm{1},\mathrm{2},...,\mathrm{1010}\right) \\ $$$${x}^{\mathrm{2}} −{x}−\mathrm{4}{z}_{{i}} ^{\mathrm{2}} =\mathrm{0} \\ $$$${for}\:{each}\:{z}_{{i}} \:{there}\:{are}\:{two}\:{roots}\:{for}\:{x}: \\ $$$${x}_{{i},\mathrm{1}} \:{and}\:{x}_{{i},\mathrm{2}} \:{with} \\ $$$${x}_{{i},\mathrm{1}} +{x}_{{i},\mathrm{2}} =\mathrm{1},\:{x}_{{i},\mathrm{1}} {x}_{{i},\mathrm{2}} =−\mathrm{4}{z}_{{i}} ^{\mathrm{2}} \\ $$$$ \\ $$$${sum}\:{of}\:{all}\:{roots}\:{for}\:{x}: \\ $$$$\Sigma{x}=\underset{{i}=\mathrm{1}} {\overset{\mathrm{1010}} {\sum}}\left({x}_{{i},\mathrm{1}} +{x}_{{i},\mathrm{2}} \right)=\underset{{i}=\mathrm{1}} {\overset{\mathrm{1010}} {\sum}}\mathrm{1}=\mathrm{1010} \\ $$$$ \\ $$$${product}\:{of}\:{all}\:{roots}\:{for}\:{x}: \\ $$$$\Pi{x}=\underset{{i}=\mathrm{1}} {\overset{\mathrm{1010}} {\prod}}\left({x}_{{i},\mathrm{1}} {x}_{{i},\mathrm{2}} \right)=\underset{{i}=\mathrm{1}} {\overset{\mathrm{1010}} {\prod}}\left(−\mathrm{4}{z}_{{i}} ^{\mathrm{2}} \right) \\ $$$$=\left(−\mathrm{4}\right)^{\mathrm{1010}} \left[\underset{{i}=\mathrm{1}} {\overset{\mathrm{1010}} {\prod}}{z}_{{i}} \right]^{\mathrm{2}} \\ $$$$=\mathrm{2}^{\mathrm{2020}} \left[\mathrm{1010}!−\frac{\mathrm{1}}{\mathrm{2}^{\mathrm{1010}} }\right]^{\mathrm{2}} \\ $$$$=\left(\mathrm{2}^{\mathrm{1010}} ×\mathrm{1010}!−\mathrm{1}\right)^{\mathrm{2}} \\ $$$$ \\ $$$$\Rightarrow{sum}\:{of}\:{all}\:{roots}\:=\mathrm{1010}\:\Rightarrow\boldsymbol{{answer}} \\ $$$$\Rightarrow{product}\:{of}\:{all}\:{roots}\:=\left(\mathrm{2}^{\mathrm{1010}} ×\mathrm{1010}!−\mathrm{1}\right)^{\mathrm{2}} \\ $$ | ||
Commented by Power last updated on 04/Feb/20 | ||
$$\mathrm{thanks} \\ $$ | ||